What Keeps Older Adults With Hearing Impairment From Adopting Hearing Aids?. (November 2018) - Tahden, Maike A. S.; Gieseler, Anja; Meis, Markus; Wagener, Kirsten C.; Colonius, Hans
The aim of this study was to compare elderly individuals who are hearing impaired but inexperienced in using hearing aids (hearing aid non-users; HA-NU) with their aided counterparts (hearing aid users; HA-U) across various auditory and non-auditory measures in order to identify differences that might be associated with the low hearing aid uptake rate. We have drawn data of 72 HA-NU and 139 HA-U with a mild-to-moderate hearing loss, and matched these two groups on the degree of hearing impairment, age, and sex. First, HA-NU and HA-U were compared across 65 auditory, cognitive, health-specific, and socioeconomic test measures as well as measures assessing technology commitment. Second, a logistic regression approach was performed to identify relevant predictors for using hearing aids. Finally, we conducted a sensitivity analysis for the matching approach. Group comparisons indicated that HA-NU perceive their hearing problem as less severe than their aided counterparts. Furthermore, HA-NU showed worse technology commitment and lower socioeconomic status than HA-U. The logistic regression revealed self-reported hearing performance, technology commitment, and the socioeconomic and health status as the most important predictors for using hearing aids.